ANALISIS KINERJA PEGAWAI DALAM MENINGKATKAN EFEKTIFITAS DINAS KETAHANAN PANGAN - Nurlinda Yani; Syahruddin; Nur Jalal; Umiyati Haris; Syahrabudin Husein Enala (PAPSEL Research and Consulting, 2024)
This study aims to understand employee performance and factors that influence organisational work effectiveness at the Food Security Office of Boven Digoel Regency. Using a qualitative approach, data was collected through in-depth interviews with key and additional informants. The results showed that there is a decline in the quality and quantity of employee performance, such as high absenteeism, lack of discipline, and vacant positions in the organisational structure. Factors affecting employee performance include technological understanding, work motivation, and work environment factors. From the perspective of organisational effectiveness, employee performance has a significant impact. A decline in individual performance can hinder the achievement of overall organisational goals. This research contributes to theoretical understanding in public administration and provides practical insights for practitioners in managing employee performance and improving organisational effectiveness in the field. The recommended improvement measures include developing technological understanding, increasing work motivation, and improving the work environment. Keywords: Employee Performance, Organisational Work Effectiveness, Performance Influencing Factors